Effect of Cold Working and Aging Treatment on Mechanical Performance of SS316LN Tube. (3rd October 2018) - Jin, H.; Wu, Y.; Qin, J.; Liu, F.; Long, F.; Yu, M.; Han, Q.; Huang, C.
Abstract: Modified stainless steel 316LN is selected as a candidate material for the China Fusion Engineering Test Reactor (CFETR) central solenoid model coil (CSMC) because of the high strength combined with good ductility at cryogenic temperature. The tensile properties, fatigue crack growth rate, and fracture toughness of the SS316LN tube in solution-annealed and aged (575°C/100 h and 650°C/100 h) conditions were evaluated at 4.2 K. The fatigue crack growth and tensile properties for the solution-annealed conduit were high enough to satisfy the design requirements for CFETR CSMC. However, the fracture toughness of the aged conduit is not satisfied, since there was a significant decline from 280 to 110 MPa·m 1/2 after cold working and aging treatments. The chemical compositions and fractures have been analyzed to assess the reason and recommend modifications that could improve fracture toughness and fatigue crack growth properties.